From Texas to Tinian and Tokyo Bay : the memoirs of Captain J.R. Ritter, Seabee commander during the Pacific War, 1942-1945 - Ritter, J. R. (James Rex), 1902-1994 (North Texas military biography and memoir series, 2019)
This is the story of J.R. Ritter (1902-1994), a civil engineer from Texas who became a U.S. Navy Seabee officer during World War II. For his memoir he preserved personal papers, letters, photos, and other items, many of which are reproduced in this book. His narrative is edited and annotated by his grandson, Jonathan Templin Ritter. The U.S. Naval Construction Battalions, known as the ""Seabees, "" were formed in March 1942. Their duties were to build military facilities and airfields overseas, in both the European and Pacific Theaters. In the Pacific Theater alone, including the Aleutians, th.